2017
DOI: 10.1080/17461391.2017.1306114
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, aetiology and prevention of musculoskeletal injuries in volleyball: A systematic review of the literature

Abstract: Currently, there is no overview of the incidence and (volleyball-specific) risk factors of musculoskeletal injuries among volleyball players, nor any insight into the effect of preventive measures on the incidence of injuries in volleyball. This study aimed to review systematically the scientific evidence on the incidence, prevalence, aetiology and preventive measures of volleyball injuries. To this end, a highly sensitive search strategy was built based on two groups of keywords (and their synonyms). Two elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
93
1
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 71 publications
3
93
1
21
Order By: Relevance
“…All prevention studies have shown to have a significant effect on reducing the risk of injury ranging from an odds ratio of 0.175 (95% CI: 0.049-0.626) for training injuries and a relative risk of 0.83 (95% CI: 0.57-1.19) achieved with FIFA 11+ prevention exercises and sport-specific balance training, relatively. The four steps of van Mechelen's 'sequence of prevention' model remain widely used when it comes to descriptive epidemiology, etiology and prevention of sports injuries [2,50]. Our results suggest that ankle and knee injuries were the most common injuries among recreational basketball players.…”
Section: Discussionsupporting
confidence: 51%
“…All prevention studies have shown to have a significant effect on reducing the risk of injury ranging from an odds ratio of 0.175 (95% CI: 0.049-0.626) for training injuries and a relative risk of 0.83 (95% CI: 0.57-1.19) achieved with FIFA 11+ prevention exercises and sport-specific balance training, relatively. The four steps of van Mechelen's 'sequence of prevention' model remain widely used when it comes to descriptive epidemiology, etiology and prevention of sports injuries [2,50]. Our results suggest that ankle and knee injuries were the most common injuries among recreational basketball players.…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, there is an agreement in the research on the use of a south-pedal orthosis, a period without body load, physiotherapy and adequate use of foot orthoses leading to complete recovery of plantar fascia rupture. 5,8,9,11 However, there is no consensus of a physiotherapeutic protocol for the treatment of this lesion. The efficacy of preventive strategies such as stretching exercises and control of the intensity of running (e.g., limiting distance, frequency, and duration) is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Leach et al 7 reported that in 6 ruptures of the plantar fascia, 5 had previously been injected. Sellman 9 reported 37 patients with ruptures, all associated with prior corticosteroid injection. Acevedo et al 5 reported 51 ruptures, with 44 cases that underwent injection therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, 3-dimensional motion capture during high impact activities, such as directional changes and landing is used to assess kinematic variables and to identify knee and ACL injury risks [8,9]. However, using such analysis for assessments is time consuming and costly; thus, it is impractical in most clinical settings.…”
Section: Introductionmentioning
confidence: 99%